1974
DOI: 10.1002/jez.1401890107
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the dental lamina in the regenerating salamander jaw

Abstract: The origin of the dental lamina (DL) in the regenerating lower jaws of seven species of larval and adult urodeles was examined by various transverse amputation procedures. Collectively the results indicate that jaw and DL regeneration following experimental amputation is a widespread phenomenon in urodeles. In 1/4 and 1/2 amputated jaws of larvae (DL present in the stump), the dental epithelium was replaced from both the anterior and posterior ends of the regenerate area, while in adults it was replaced from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

1978
1978
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 7 publications
0
20
0
1
Order By: Relevance
“…It has been reported that dentary bone regenerates and fuses at the center of the mandible in newts 6 months after amputation, as demonstrated using 2-dimensional X-ray analysis (Graver, 1974). We detected the regenerated dentary bone fused at the center of the mandible and also regenerating teeth in more detail using 3-dimensional analysis (Fig.…”
Section: Usefulness Of Micro-ct For Amphibian Regeneration Researchmentioning
confidence: 80%
“…It has been reported that dentary bone regenerates and fuses at the center of the mandible in newts 6 months after amputation, as demonstrated using 2-dimensional X-ray analysis (Graver, 1974). We detected the regenerated dentary bone fused at the center of the mandible and also regenerating teeth in more detail using 3-dimensional analysis (Fig.…”
Section: Usefulness Of Micro-ct For Amphibian Regeneration Researchmentioning
confidence: 80%
“…In aquatic o teichthyan , tooth germs can derive directly from the oral or pharyngeal epithelium without an intervening dental lamina ( 114,170,(253)(254)(255). It is well po sible that the fir t tooth germs to develop in a dentition are always derived directly from the superficial epithelium, rather than indirectly from a dental lamina, as ha been reported for tel o ts ( 46,152,169,240), larval urodeles ( 256) and embryonic crocodile ( 1 19, 121, 171 ). Thi po ibly reflect the ance tral condition as in odontode development (p. 448).…”
Section: F1111iotionmentioning
confidence: 84%
“…Both larval Ambystoma maculatum and adult newt mandibles regenerated alveolar cartilage and bone across the gap after removal of one-quarter or one-half of the mandible, 77 suggesting that there is no CSD for regeneration in the urodele mandible. In A. maculatum larvae, the dental lamina containing the toothforming epithelium regenerated in both anterior and posterior directions over the regenerated bone, but the adult newt dental lamina exhibited polarity of regeneration, being regenerated only in a posterior direction.…”
Section: Discussionmentioning
confidence: 99%
“…75,[77][78][79][80] Jaw regeneration takes longer than limb regeneration, about 24 weeks compared to only 4-6 weeks for the limb. Only the tooth bearing skeletal element, the dentary of the maxilla and mandible, is ossified 5 months after amputation.…”
Section: Radiograms Of Control (A B A' and B') And Ra-treated (Cmentioning
confidence: 99%